Aplikasi Surat Pertanggung Jawaban Kegiatan Dana Bantuan Operasional Kesehatan Pada Puskesmas Bati – Bati Berbasis Web - Agustian Noor; Arif Supriyanto (Infotek: Jurnal Informatika dan Teknologi, 2022)
In the national and political unitary body in Tanah Laut district, there is actually a system created to deal with staffing problems in the environment. However, there are still many shortcomings in the system. The first thing is seen in the retirement status of employees, in this information system there is no feature that can know when the employee retires, this is clearly very detrimental to the national and political unitary body of Tanah Laut Regency, because retired employees may still be registered in the system So far, the admin cannot know when the employee will retire, because there is no feature made to find out this information. Based on the description of the explanation, it is necessary to develop a personnel information system that can manage pension data and manage class data on a regular basis. . In developing the application, the author uses the waterfall method using the PHP programming language (Framework CodeiIgniter), HTML, CSS, JavaScript, and is designed using Entity Relationship Diagrams, Data Flow Diagrams and Flowcharts. This application is expected to be able to assist in viewing the data of retired employees. Keywords: Information Systems, Employees, Retirement, and Development.